European solidarity in times of crisis: the role of information and media use. Issue 5 (19th September 2021) - Goldberg, Andreas C.; Gattermann, Katjana; Marquart, Franziska; Brosius, Anna; de Vreese, Claes H.
Abstract: COVID-19 has important implications for European solidarity. In this study, it is proposed to consider the role of information and media use for citizens' attitudes towards European solidarity given the accelerated information supply alongside an increase in information-seeking behaviour among citizens. These factors have previously received little attention in the extant literature. In particular, we examine three dimensions of transnational solidarity (fiscal, medical and border solidarity) and present results from a four-wave panel survey conducted in the Netherlands between April and July 2020. It will be shown that solidarity support changes as the pandemic unfolds. Variation in general media use is only marginally related to solidarity, possibly due to an increase in media use during the pandemic. Yet, there are some effects at the media outlet level, particularly for newspaper reading. This research note highlights important implications for future research on European solidarity during and in the aftermath of crises.